2012
DOI: 10.4067/s0034-98872012000400015
|View full text |Cite
|
Sign up to set email alerts
|

Perspectiva evolucionista de los trastornos de la conducta alimentaria

Abstract: Evolutionary theory has contributed with physiological, psychological and behavioral explanations to the comprehension and treatment of eating disorders (ED). The aim of this review is to analyze the relationship between ED and the attachment theory and natural selection based hypotheses (famine fl ight, reproductive suppression and intrasexual competition. Entre las diversas aproximaciones que han contribuido a la comprensión de estas patologías, la teoría evolucionista aporta una síntesis de explicaciones fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…These results with regard to anxiety and depression support García-Villamisar et al's (2012) findings that in people with ED or AR-ED, depression indexes were Eating Problems 7 higher than in the general population, possibly because depression makes people more susceptible to developing ED. Differences between AR-ED and WR-ED patients on the variables accompanying the EDI were found in earlier studies, too, particularly ineffectiveness, perfectionism, maturity fears, interoceptive awareness, interpersonal distrust, and impulsivity (Behar, 2012;Lundahl et al, 2015;Sehm & Warschburger, 2015). However the present study found differences in all the accompanying variables, suggesting AR-ED participants display tremendous clinical alteration.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…These results with regard to anxiety and depression support García-Villamisar et al's (2012) findings that in people with ED or AR-ED, depression indexes were Eating Problems 7 higher than in the general population, possibly because depression makes people more susceptible to developing ED. Differences between AR-ED and WR-ED patients on the variables accompanying the EDI were found in earlier studies, too, particularly ineffectiveness, perfectionism, maturity fears, interoceptive awareness, interpersonal distrust, and impulsivity (Behar, 2012;Lundahl et al, 2015;Sehm & Warschburger, 2015). However the present study found differences in all the accompanying variables, suggesting AR-ED participants display tremendous clinical alteration.…”
Section: Discussioncontrasting
confidence: 58%
“…Differences between AR-ED and WR-ED patients on the variables accompanying the EDI were found in earlier studies, too, particularly ineffectiveness, perfectionism, maturity fears, interoceptive awareness, interpersonal distrust, and impulsivity (Behar, 2012; Lundahl et al, 2015; Sehm & Warschburger, 2015). However the present study found differences in all the accompanying variables, suggesting AR-ED participants display tremendous clinical alteration.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Likewise, results of previous reviews did not reveal conclusive data on the existence of an association between specific attachment patterns and ED subtypes [2,3]. For instance, while some authors [79,80] have found an association between avoidant attachment and AN, and anxious attachment and BN, others claim that most people with ED have either an avoidant attachment [81] or an anxious insecure attachment [82]. In light of these findings, further research should perform mediating analyses distinguishing between different diagnoses of ED, as the indirect effect of specific mediating mechanisms might be different regarding the nature of the symptomatology (e.g., emotion dysregulation might have a greater impact on bulimic symptoms).…”
Section: Discussionmentioning
confidence: 96%